Manajemen Inventaris Real-Time dengan Sistem Inventaris Abadi dalam Rantai Pasokan Modern - Dedi Gunawan; Tri Agus Setiawan (Jurnal Nasional Teknologi Komputer, 2021)
This article explores the implementation of a perpetual inventory management system at 786 Vabe Store, aimed at improving operational efficiency and decision-making capabilities in the modern supply chain. The study begins by discussing the critical role of effective inventory management in today’s fast-paced business environment, emphasizing the benefits of real-time data tracking and increased accuracy in inventory records. The study used a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess the impact of the system on the inventory process. The methodology follows a structured Waterfall Model, encompassing the stages of system design, analysis, and testing. Key findings highlight the successful integration of user-friendly interfaces for data input and reporting, including modules for item entry, user management, supplier information, and sales transactions. Each interface is designed to facilitate seamless interaction, ensuring that staff can efficiently manage inventory and sales processes. Results show significant improvements in transaction processing efficiency and data management. The implemented system has comprehensive output capabilities, allowing users to generate a variety of reports, such as daily, monthly, and annual sales reports, as well as purchasing and inventory reports. These outputs provide valuable insights into sales performance and inventory levels, supporting informed decision making. In conclusion, this study shows that the implementation of a perpetual inventory management system not only streamlined operations at 786 Vabe Store but also improved overall performance, underscoring the importance of integrated inventory solutions in the modern retail environment.